Correlation between lung injury score, PvO2/FiO 2 ratio and oxidative stress markers in tracheal aspirate samples in intubated infant patients during chest physical therapy - Leelarungrayub J. (2017)
© 2017, Archives of Pediatric Infectious Diseases. Background: Pneumonia presents high oxidative stress, which directly affects the lung injury and oxygenation status. Evidence has shown the correlation of oxidative stress markers in tracheal aspirates (TA) in infant patients, however, not before or after chest physical therapy (CPT). Objectives: The objective of this study was to evaluate the correlation between lung injury score (LIS) or PvO 2 /FiO 2 ratio and oxidative stress parameters in TA before and after CPT in infant patients during recovery from pneumonia. Methods: TA samples from 40 intubated patients aged 5.4 ± 0.15 months were collected before and after CPT for evaluating oxidative stress parameters; as a glutathione (GSH), vitamin E, hyarulonic acid (HA), and malondialdehyde (MDA). Furthermore, the LIS and PvO 2 /FiO 2 ratio were recorded. The correlation between oxidative stress markers and LIS or PvO 2 /FiO 2 ratio was evaluated before and after CPT. Results: The results before CPT showed no significant correlation between LIS and all parameters, whereas, the PvO 2 /FiO 2 ratio correlated with the thiol group (r = -0.566, P = 0.000) and HA (r = -0.507, P = 0.000). After CPT, LIS correlated with GSH and HA (r = -0.396 and -0.409, P = 0.01) and the PvO 2 /FiO 2 ratio correlated significantly with the GSH, HA, and MDA (r = 0.609, 0.768, -0.482, P = 0.000). Conclusions: Some oxidative stress markers, such as the GSH, HA, and MDA in TA possibly reflected lung injury and oxygenation and may respond with more correlation after CPT intervention than before it.